Peningkatan Hasil Belajar IPA Melalui Implementasi Model Pembelajaran Discovery Learning di Sekolah Dasar Kota Banda Aceh - Lili Kasmini; Ilfiana Munthe (Universitas Kanjuruhan Malang, 2021)
Science is learning that is very closely related to human life, many natural instruments are directly involved in teaching and learning processes. One of the objectives of this study is to see the effect of the Discovey Learning model on student learning outcomes, the Discovery Learning learning model is a learning process that can involve mentally and physically students, so that the learning obtained can last a long time in the memory of students. This research was conducted at SD N 55 Banda Aceh, after observing the learning process of students showing less than optimal results. It can be seen from the learning outcomes before the application of the Discovery Learning model the average learning outcomes are 37 while the average obtained after the application of the Discovey Learning Model is 73. In addition, based on the results of the calculation of the hypothesis that have been determined by the hypothesis acceptance rules, accept Ha If tcount> ttable, the results obtained are degrees of freedom (dk = n-1 = 34-1 = 33) and the significant value is α = 0.05, for this calculation the t-table is 2.19. From the above calculations using the t-test shows that tcount> ttable (2.19> 1.697). The results of the analysis of the average N-gain obtained reached 50 which was categorized as moderate.